Evaluation of the Antibacterial Activity of Muntingia calabura L. Leaf Extract in Anti-Acne Serum and Gel Moisturizer Formulations - Andi Ulfah Magefirah Rasyid; Nurfadilah Nurfadilah; Fityatun Usman; Zulkifli Zulkifli; Zulham Zulham; Asril Burhan (Tropical Biopharmaca Research Center, IPB University, 2026)
The cherry tree (Muntingia calabura L.) is known to contain bioactive compounds such as flavonoids, tannins, and saponins, which exhibit potential as natural antibacterial agents against acne-causing bacteria. This study aimed to evaluate and compare the antibacterial efficacy of serum and moisturizer gel formulations containing ethanol extract of M. calabura leaves against Propionibacterium acnes. Serum was selected due to its high concentration of active ingredients and superior skin penetration, while the gel moisturizer provides a light, non-greasy texture that is comfortable and easily absorbed. The results demonstrated that the serum formulation containing 18% extract (F3) exhibited the highest antibacterial activity against P. acnes, with a strong inhibition zone. Similarly, the gel formulation with 6% extract (F3) also showed a strong inhibitory effect. These findings highlight the potential of M. calabura leaf extract as an effective natural agent for the development of topical anti-acne skincare products.